2007
DOI: 10.1055/s-2007-966990
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation improves intubation depth in double-balloon enteroscopy: a randomized, controlled, double-blind trial

Abstract: CO (2) insufflation significantly extended intubation depth in DBE. CO (2) insufflation also reduces patient discomfort. CO (2) insufflation may lead to a higher diagnostic and therapeutic yield of DBE, with reduced patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 14 publications
3
120
3
2
Order By: Relevance
“…The usefulness and safety of CO2 as an alternative to air in patients who undergo diagnostic or therapeutic endoscopy under conscious or intravenously sedated conditions have been demonstrated in several randomized controlled studies [1][2][3][4][5][6] . No pulmonary complications or CO2 retention have reportedly occurred from CO2 insufflation in patients without some type of pulmonary dysfunction, and no adverse event related to CO2 insufflation developed in the present study either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness and safety of CO2 as an alternative to air in patients who undergo diagnostic or therapeutic endoscopy under conscious or intravenously sedated conditions have been demonstrated in several randomized controlled studies [1][2][3][4][5][6] . No pulmonary complications or CO2 retention have reportedly occurred from CO2 insufflation in patients without some type of pulmonary dysfunction, and no adverse event related to CO2 insufflation developed in the present study either.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, CO2 insufflation during diagnostic or therapeutic endoscopy has been shown to be safe and effective in reducing procedure-related pain and discomfort [1][2][3][4][5] . The safety of CO2 insufflation for endoscopic submucosal dissection (ESD) has also been shown in several studies [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide insufflation instead of using ambient air increases intubation depth and significantly reduces inconvenience of the patient and may therefore be preferred for all balloon-enteroscopy interventions. 8,9 In comparison to spiral enteroscopy, the examination time was reduced with use of the spiral, although the insertion depth with DBE was superior.…”
Section: Introductionmentioning
confidence: 99%
“…The results of all of these RCTs were unambiguous, with significantly less pain reported after CO2 colonoscopy [3][4][5][6][7] . For other endoscopic procedures also, CO2 was found to be superior to air: (1) for double balloon enteroscopy, small bowel intubation is deeper [8] ; (2) for endoscopic retrograde cholangio-pancreatography (ERCP), postprocedural pain is less [9,10] ; and (3) for complex colorectal procedures (endoscopic submucosal dissection), fewer sedative drugs are required [11] . This is explained by the pathophysiology of gases: intestinal gases leave the body through alimentary orifices and exhaled air (gases can diffuse through the gut into splanchnic blood and subsequently pulmonary circulation).…”
Section: Introductionmentioning
confidence: 99%